Videovsebine v šoli in ob tekmovanju iz znanja slovenščine Slovenščina ima dolg jezik - Nidorfer-Šiškovič, Mojca (Jezik in slovstvo, 2012)
In the article, we provide argumentation in support of a new competition in the knowledge of the Slovene language entitled ŽSlovene Has a Big MouthŽ organised by the Science to the Youth section of the Slavic Society of Slovenia. The design of the competition is such that it takes into account the spread and use of contemporary media in the lives of children and young adults, while at the same time emphasizing the importance of in-depth engagement with literary texts and a more rigorous team preparation of the competition products. In the frst competition, entitled Literature on Film, primary and upper secondary school pupils will compete in the preparation of a short film based on a selected literary text. The choice of this particular content places the emphasis on complexity, given that in the process of reproduction the literary and filmic elements come together. The designers of the competition presuppose that this is precisely what pupils and teachers will be attracted and motivated by.
Keywords: Slovenščina ima dolg jezik; Slovene; slovenščina; Slovene literature; slovenska književnost; film v izobraževanju; šolska tekmovanja